Analysis of Cash and Inventory Turnover in Improving Profitability - Maya Sari; Andriyani Andriyani (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2021)
Research conducted by the author aims to analyze cash flows and inventory turnover to increase profitability as measured by Return On Assets (ROA) at PT. Perkebunan Nusantara III (Persero) Medan. The approach used in this research is a descriptive approach. Data collection techniques in this study using documentation study. The data analysis technique used in this research is descriptive analysis technique. Where in this study to analyze cash turnover and inventory turnover in increasing Return On Assets (ROA). The results showed that cash turnover and inventory turnover were not optimal in increasing profitability. The cash turnover has decreased while the profitability has increased. The decrease in cash turnover was due to the relatively small amount of cash owned by the company and an increase in the amount of unproductive funds that were embedded in the company's cash. The decrease in inventory turnover was caused by piling up inventory and decreasing sales volume. Profitability as measured by the company's Return on Assets (ROA) has decreased due to the decline in the company's ability to generate net income from 2013 to 2015 followed by an increase in company assets. The decrease in cash turnover was due to the relatively small amount of cash owned by the company and an increase in the amount of unproductive funds that were embedded in the company's cash.